ROLE AND FUNCTIONS OF BAWASLU OF THE REPUBLIC OF INDONESIA IN THE GENERAL ELECTION SYSTEM IN INDONESIA - Deni Syaputra; Feby Adriani; Yusmiarni, Yusmiarni; Yuni Andriani (Ikatan Dosen Menulis, 2025)
Accountability for holding elections must be accountable for the implementation of their duties and authorities to the public, both politically and legally. Being politically responsible means that every element involved in holding elections has an obligation to explain to the public their functions and the reasons for the actions taken. Being legally responsible means that any party suspected of violating the law regarding the principles of democratic elections must submit to the law enforcement process based on the principle of the presumption of innocence and the principle of due process of law regulated in the Criminal Procedure Code. is that the holding of elections is carried out by independent institutions.